Difusión gastronómica y su incidencia en el desarrollo sostenible del cantón Las Naves año 2021 - Garcia Verdezoto, Angie Silvana (2022)
Currently, gastronomic tourism has become an important part of the financial development of cities, with reference countries such as Mexico, Peru, Italy, Colombia that offer a unique gastronomic diversity, which is included as a tourist attraction in the itineraries offered to tourists. , thus changing the way of doing tourism, where gastronomy is no longer a purely survival activity, to be a leisure and enjoyment activity, positioning itself in this way in one of the favorites of tourists worldwide. Las Naves offers a typical gastronomy that is part of its cultural expression, a tradition that has been kept alive, a mixture of ancestral flavors that identify its people and that must be transmitted to the community. In the canton from the early hours of the morning several of the families dedicate themselves to the work in the preparation depending on tourism for their sales, being their main source of income, which also generates employment and reactivates the commerce of the area for which it is essential to spread promoting the economic development of its people.